Whole Body Vibration Exposure on Markers of Bone Turnover, Body Composition, and Physical Functioning in Breast Cancer Patients Receiving Aromatase Inhibitor Therapy: A Randomized Controlled Trial. (September 2018) - Baker, Michael K.; Peddle-McIntyre, Carolyn J.; Galvão, Daniel A.; Hunt, Catherine; Spry, Nigel; Newton, Robert U.
Introduction: Women with breast cancer are often prescribed aromatase inhibitors, which can cause rapid loss of bone mass leading to significant potential for morbidity. Vibration training has been shown to be helpful in reducing bone turnover in postmenopausal women without cancer.Aim: To examine the effect of vibration stimulus on markers of bone turnover in breast cancer patients receiving aromatase inhibitors.Methods: Thirty-one breast cancer survivors undergoing treatment with aromatase inhibitors were randomized to vibration stimulus (n = 14) or usual care control (n = 17). Low-frequency and low-magnitude vibration stimulus (27-32 Hz, 0.3 g ) was delivered in supervised sessions via standing on a vibration platform for 20 minutes, 3 times per week for 12 weeks. The primary outcome was blood markers of bone resorption (serum N-telopeptide X/creatine) and formation (serum type 1 procollagen N-terminal propeptide; P1NP). Other study outcomes body composition as well as measures of physical functioning. Outcomes were compared between groups using analysis of covariance adjusted for baseline values as well as time on aromatase inhibitors.Outcomes: On average, participants were 61.5 years old and overweight (ie, body mass index = 28.5 kg/m 2 ). Following vibration training, there was no significant difference between groups for bone resorption (adjusted group difference 0.5, P = .929) or formation (adjusted group difference 5.3, P = .286). There were also no changes in any measure of physical functioning body composition.Conclusions: Short-term low-magnitude vibration stimulus does not appear to be useful for reducing markers of bone turnover secondary to aromatase inhibitors in breast cancer patients; nor is it useful in improving physical function or symptoms. However, further investigations with larger samples and higher doses of vibration are warranted.Trial Registration: Australian and New Zealand Clinical Trials Registry (ACTRN12611001094965).